Effects of Fine Motor Development in the Subsequent Expressive and Receptive Language Skills of Children with Special Needs - David Karlo I. Equipaje; Deborah Natalia E. Singson (Philippine Social Science Journal, 2020)
Studies related to developmental psychology have long recognized the importance of motor development but have recently begun to systematically map out its subsequent developmental pathways.  In many international studies, finding evidence on the effects of fine motor skills development on children's language skills with special needs (CSNs) has significantly grown much interest.  Fine motor skills and language skills play a vital role in a child's early development.  Hence, the study describes the level of performance in the fine motor domain, expressive language domain, and receptive language domain of preschool-aged CSNs of a private intervention center in Bacolod City during the school year 2019-2020. Likewise, it explores the existing relationship of the fine motor skills and language skills between the CSN's age and sex before and after participating in a fine motor development program.  Also, it determines the subsequent consequences of the fine motor development program on the expressive language skills and receptive language skills of the CSNs.